Sistem Pakar Dalam Menganalisa Penyakit Perut Dengan Menggunakan Metode Certainty Factor - Annisa Amalia; Gunadi Widi Nurcahyo; Y Yuhandri (SEULANGA SYSTEM PUBLISHER, 2021)
Food technology that is increasingly advanced makes people tend to consume fast food, as well as foods that contain chemicals. This causes the tendency of an unhealthy lifestyle and becomes one of the factors that cause stomach disease. Stomach disease can be experienced at the age of children to adulthood. Unhealthy lifestyle means eating patterns that are initially consumptive on healthy foods and then turn into consumptive foods that are less healthy. Not only food, rarely exercise is also likely to cause pain in the stomach. Diagnosing stomach disease is still carried out by conducting face-to-face consultations with health workers, which can take a long time and cost a lot of money. Lack of information on stomach disease sufferers about the symptoms of stomach disease, causes patients not to know the type of stomach disease they are experiencing. This is the goal of research that will build an expert system software that is expected to be able to analyze stomach diseases and help the community, stomach sufferers and health workers in diagnosing types of stomach diseases. The method used in this study is Certainty Factor (CF) or the certainty value of a disease. Expert system software development is done by analyzing software requirements, system user needs. The dataset of this study is the symptoms and types of stomach diseases that occur at the Salido Health Center. The result of the system built is the result of the diagnosis of stomach disease with the percentage of certainty value from the calculation using Certainty Factor. The system will also provide information about the description, causes and prevention of the types of stomach diseases diagnosed. With the construction of an expert system of stomach diseases, it is hoped that this research can be a reference for users in diagnosing stomach diseases. The accuracy results obtained after testing the system is 80%.